2005
DOI: 10.1080/15287390590921757
|View full text |Cite
|
Sign up to set email alerts
|

Iron Release and Oxidative DNA Damage in Splenic Toxicity of Aniline

Abstract: Mechanisms by which aniline produces selective toxicity to the spleen are not well understood. Previously, studies showed that aniline exposure induces lipid peroxidation and protein oxidation in the spleen. The present study was aimed to determine the release of free iron and oxidative DNA damage in the spleen following aniline exposure. To achieve this, male SD rats were orally administered 1 mmol/kg/d aniline for 7 d, while controls received the vehicle only. Total splenic iron content showed a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 34 publications
4
38
1
Order By: Relevance
“…Therefore, it is critical to delineate the early molecular events in the spleen, which could potentially lead to splenic fibrosis and/or fibrosarcoma. Using an experimental condition known to generate oxidative stress and that precedes splenic fibrosis (Khan et al, 1997a(Khan et al, , 2003bWu et al, 2005), this study provides evidence that repeated-dose aniline exposure leads to activation of NF-κB and AP-1, causes phosphorylation of upstream critical signaling proteins [IKKα/β and MAPKs (ERK1/2, JNK1/2 and p38)], and results in the upregulation of pro-inflammatory and pro-fibrogenic cytokines in the spleen. These early molecular events could ultimately lead to splenic fibrosis and/or fibrosarcomas.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Therefore, it is critical to delineate the early molecular events in the spleen, which could potentially lead to splenic fibrosis and/or fibrosarcoma. Using an experimental condition known to generate oxidative stress and that precedes splenic fibrosis (Khan et al, 1997a(Khan et al, , 2003bWu et al, 2005), this study provides evidence that repeated-dose aniline exposure leads to activation of NF-κB and AP-1, causes phosphorylation of upstream critical signaling proteins [IKKα/β and MAPKs (ERK1/2, JNK1/2 and p38)], and results in the upregulation of pro-inflammatory and pro-fibrogenic cytokines in the spleen. These early molecular events could ultimately lead to splenic fibrosis and/or fibrosarcomas.…”
Section: Discussionmentioning
confidence: 85%
“…The choice of aniline dose was based on our earlier short-term studies that showed iron overload, and significant increases in lipid peroxidation, protein oxidation and DNA damage (oxidative stress) in the spleen (Khan et al, 1997a(Khan et al, , 2003bWu et al, 2005). Twenty four hours following the last dose, the animals were euthanized under nembutal (sodium pentobarbital) anesthesia and spleens were aseptically removed immediately, blotted, and weighed and then used for various analyses.…”
Section: Animals and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations